2020
DOI: 10.1111/ggi.14085
|View full text |Cite
|
Sign up to set email alerts
|

Low prevalence of radiographic hip osteoarthritis and its discordance with hip pain: A nationwide study in Korea

Abstract: AimThis study aimed to evaluate the prevalence and associated factors of radiographic hip osteoarthritis (OA) in the Korean community‐dwelling population.MethodsThis study included 11 814 individuals (5025 men and 6789 women) ≥50 years of age from the Korea National Health and Nutrition Examination Surveys. Radiographic hip OA was defined as having a Kellgren–Lawrence grading scale score ≥2. Painful hip OA was defined as radiographic hip OA with the presence of hip pain. The prevalence of radiographic hip OA w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 31 publications
1
12
2
Order By: Relevance
“…This showed only a marginal effect on the ORs, suggesting that hip pain is not associated with a higher likelihood of having hip ROA in the contralateral pain-free hip. However, in a prior study, knee pain was associated with hip ROA (17), which could indicate that our observed association might underestimate the true relation in the population or that the OR of knee pain is simply different from contralateral hip pain. Secondly, we used radiographic K&L scores in our analyses that were read and scored with images paired and in known sequence (26).…”
Section: Strengths and Limitationscontrasting
confidence: 55%
See 3 more Smart Citations
“…This showed only a marginal effect on the ORs, suggesting that hip pain is not associated with a higher likelihood of having hip ROA in the contralateral pain-free hip. However, in a prior study, knee pain was associated with hip ROA (17), which could indicate that our observed association might underestimate the true relation in the population or that the OR of knee pain is simply different from contralateral hip pain. Secondly, we used radiographic K&L scores in our analyses that were read and scored with images paired and in known sequence (26).…”
Section: Strengths and Limitationscontrasting
confidence: 55%
“…In prior research, definitions for definite and severe ROA differed considerably, as did pain definitions. Hence, the odds ratios (OR) differed substantially, ranging from 1.6 to 123.4 for severe and 1.3 to 2.8 for definite ROA (16,17,19). Since the symptomatic hip ROA prevalence was low in these studies, results were imprecise.…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…In this same study, those with worsening hip structure also had less hip extension, although not significantly so. The presence of structural damage is not tightly linked to hip pain (Birrell et al, 2005 ; Heerey et al, 2018 ; Park et al, 2021 ). Worsening pain has been associated with limited hip extension and external rotation during walking in females with mild to moderate hip OA (Tateuchi et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%